Acute Ethanol Inhibition of γ Oscillations Is Mediated by Akt and GSK3β - Wang, JianGang; Zhao, JingXi; Liu, ZhiHua; Guo, FangLi; Wang, Yali; Wang, Xiaofang; Zhang, RuiLing; Vreugdenhil, Martin; Lu, Chengbiao (Frontiers in Cellular Neuroscience, 2016)
Hippocampal network oscillations at gamma band frequency (γ, 30-80 Hz) are closely associated with higher brain functions such as learning and memory. Acute ethanol exposure at intoxicating concentrations (≥50mM) impairs cognitive function. This study aimed to determine the effects and the mechanisms of acute ethanol exposure on γ oscillations in an in vitro model. Ethanol (25-100 mM) suppressed kainate-induced γ oscillations in CA3 area of the rat hippocampal slices, in a concentration-dependent, reversible manner. The ethanol-induced suppression was reduced by the D1R antagonist SCH23390 or the PKA inhibitor H89, was prevented by the Akt inhibitor Triciribine or the GSk3β inhibitor SB415286, was enhanced by the NMDA receptor antagonist D-AP5, but was not affected by the MAPK inhibitor U0126 or PI3K inhibitor wortmanin. Our results indicate the intracellular kinases Akt and GSk3β play a critical role in the ethanol-induced suppression of γ oscillations and reveal new cellular pathways involved in the ethanol-induced cognitive impairment.